Compreensão das mudanças no uso do solo e na acessibilidade ao trabalho da população de baixa renda em Fortaleza - Castro, Isabela Ribeiro de (2019)
Due to the existing spatial disconnection between dwelling-places and job opportunities, large cities around the world, and particularly in developing countries, have faced a challenging problem that strikes the vulnerable social stratum of their societies. That phenomenon has been object of specialized literature since the 80’s, being appropriately known as Spatial Mismatch due to the Spatial Mismatch Hypothesis. In Brazil, that phenomenon has been usually related with inequality problems in low-income people’s levels of job accessibility, since this group’s options of residential location and modes of transport are mostly limited. In that way, having the beginning of the present century as the time frame, and the city of Fortaleza (Brazil) as a geographic frame, the main goal of this dissertation is to understand the changes on low income people’s job accessibility, from the perspective of the changes in the land use urban subsystem. The achievement of this main objective is based on an interdisciplinary planning approach that advocates for integrated analysis of transport and land use subsystems. Methodologically, it is proposed the characterization of the Spatial Mismatch and the inequalities in job accessibility levels of the low income population in Fortaleza, starting from a representation of this problem. The characterization is carried out by the collection and operational modeling of indicators, followed by the analytical investigation of their spatial results, in the aforementioned time interval. The research brings phenomenological contributions regarding the understanding of the interactions, over time, between several types of accessibility inequalities and urban changes in the land use subsystem, for a social group considered more vulnerable. Moreover, it represents a methodological advance regarding the characterization of distinct and interrelated urban phenomena, which is a fundamental step in the process of integrated planning of transport and land use, since it proposes the characterization of its evolution, comprising: them in different time scenarios.